Analysis of Clinical Trials of New Drugs for Liver Diseases in China - Lin L; Li H (Dove Medical Press, 2021)
Longfei Lin, Hui Li Institute Chinese materia medica china academy of Chinese medical sciences, Beijing, People's Republic of ChinaCorrespondence: Hui LiInstitute Chinese materia medica china academy of Chinese medical sciences, Dongcheng District Dongzhimen Nanxiaojie Within 16, Beijing, People's Republic of ChinaTel + 86 1064087670Fax + 86 1064032658Email lihuizys@126.comBackground: Liver diseases are a major public health concern worldwide, and the development of novel therapeutic drugs is an important research focus. But no overview has been conducted so far on the current research and development for liver-specific drugs in China, and the actual situation regarding the development and evaluation of new drugs in clinical trials.Methods: The information of all clinical trials on liver diseases were obtained through the "Pharmaceutical Clinical Trial Registration and Information Disclosure Platform" before December 31, 2020.Results: A total of 751 clinical trials on liver disease-related drugs were published on the above platform, including 574 chemical drugs, 128 biological products, and 49 traditional Chinese medicine (TCM)/natural drugs. The number of annual registrations has increased on an annual basis. The main indications for these clinical trials are viral hepatitis, liver malignancies, liver abscess, liver transplantation, congenital liver metabolic disease, and other hepatitis-related diseases. Hepatitis B, hepatitis C and liver cancer accounted for 72.4% of the total clinical trials, and the majority are related to generic drug research. There are 103 innovative drugs currently in clinical testing, mainly for hepatitis B, hepatitis C and hepatocellular carcinoma.Conclusion: The stronger macro-control is required for the clinical trials conducted in China, and it is necessary to identify new therapeutic targets and develop novel drugs for the key liver diseases, as well as preventive hepatitis C vaccines, and targeted therapy, TCM/natural drugs and immunotherapy for liver cancer.Keywords: clinical trials, liver diseases, hepatitis B, hepatitis C, liver cancer